A cut too deep? A qualitative enquiry into the experience of multiple organisational restructurings in the South African oil industry: a case study - Tooke, Janet (School of Management Studies, 2018)
This dissertation reports the findings of a study which sought to investigate the experiences of people who were exposed to multiple restructurings in the South African oil industry. Although there is a substantial amount of research on restructurings worldwide, an extensive review of available literature highlighted a dearth of research on multiple restructurings. Investigation of this research question was undertaken using a case study and qualitative research method. In-depth interviews of six employees of an oil company in South Africa were undertaken. Through these interviews, the personal experiences of employees who had been exposed to multiple restructurings were analysed. Similarly, interviews were undertaken with two members of senior management responsible for the implementation of a number of the restructurings. Their interview responses provided insight into the company's rationale for undertaking multiple restructurings. The results of the research indicated that distrust and cynicism grew amongst employees with repeated exposure to restructurings. The interview participants perceived that many remaining employees suffered from feelings of survivor's guilt and low morale and results indicated that the company did little to assist these employees to cope with these feelings. The research findings indicated that loss of corporate memory created role ambiguity and tension between departments as portfolios were redistributed amongst employees. Employee workloads were dramatically increased resulting in further stress and stress-related health problems, absenteeism and resignation. Participants of the research believed that the senior leadership team were ill-equipped to run a restructuring process and the employee consultation process appeared to do nothing to improve employees' trust in management. The results of this research highlighted the perception of the participants that repeated restructurings fail to achieve performance improvement at companies. Instead, the results indicated that repeated restructurings appear to lead to poor employee morale, resultant poor productivity and a high level of intention to quit. Companies should explore alternatives before embarking on a restructuring process as a first choice to alleviate cost pressures (Burke and Nelson, 1997; Von Krogh & Kameny, 2002). Where restructuring is inevitable, it is a recommendation of this research that training and counselling of remaining employees be given priority to assist with the management of stress and other symptoms of survivor sickness.